Patterns of injury and death in mass casualty incidents from 2013 to 2018 in Mogadishu, Somalia Mass casualty incidents in Mogadishu, Somalia - Nor, Mahad Abdullahi; Sonmez, Recep Ercin; Hassan, Mohamed Yusuf; Ozsoy, Mehmet Sait; Alimoglu, Orhan (Bangladesh Journal of Medical Science, 2023)
Objective: Mass casualty incidents (MCI)s are a serious threat to public health in Mogadishu, Somalia. The present study aims to demonstrate the patterns of injury and clinical outcomes in MCIs in Mogadishu, Somalia. Methods: This is a retrospective, cross-sectional analysis of clinical data retrieved from patients involved in MCIs between 2013 and 2018 in Mogadishu, Somalia. Patient demographics were statistically analyzed with the anatomical site of injury, mechanism, and types of injury to find any meaningful association among each other in terms of clinical outcomes. Results: Four hundred (M/F: 62%/38%) cases were included in the present study. There was a significant association between the mechanism of injury and incidence of mortality (95% CI = 0.028-6.65) (p=0.02). Another significant association found was between the clinical presentation of injury and mortality rate of which the presence of external/or internal bleeding was highly associated with death (95% CI = 0.640- 3.163; OR:1.423) (p=0.02). Conclusion: Prompt precautions should be taken by improving awareness of the public through educational programs, preparing campaigns in coordination with the ministry of health, and influencing the power of the media should be used to reach everyone in the society. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 323-328